2007
DOI: 10.4012/dmj.26.746
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Bond Strength of Er, Cr: YSGG Laser-irradiated Human Dentin to Composite Inlays with Two Resin Cements

Abstract: The purpose of this study was to investigate the tensile bond strength of composite inlays to human dentin with two different cavity preparation tools (bur versus Er, Cr: YSGG laser) and with two different bonding procedures (total-etch: Variolink II versus self-etch: Maxcem). The specimens were divided into four groups: bur-cut/Variolink II, bur-cut/Maxcem, laser-ablated/Variolink II, and laser-ablated/Maxcem. The following characteristics were then investigated: morphological change, dentin-resin cement inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Whereas Nagase et al [28] found that the bond strength using a glass fiber post and total-etch adhesive system in combination with dual-cured resin cement was similar to that in the control group after Er,Cr:YSGG (0.75W) or Nd:YAG + Er,Cr:YSGG laser irradiation, the Nd:YAG (1.5W) laser alone was shown to negatively affect the post retention force. Other studies [29,30] showed the negative effect of Er,Cr:YSGG laser irradiation on the adhesion of resin to dentin with various adhesive systems; however, acid-etching [29] after laser irradiation increased the tensile strength of the bond to dentin. In the present study, there was no difference between the Er,Cr:YSGG laser irradiation (1W, 2W and 3W) groups and the untreated group, regardless of the different root levels.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Whereas Nagase et al [28] found that the bond strength using a glass fiber post and total-etch adhesive system in combination with dual-cured resin cement was similar to that in the control group after Er,Cr:YSGG (0.75W) or Nd:YAG + Er,Cr:YSGG laser irradiation, the Nd:YAG (1.5W) laser alone was shown to negatively affect the post retention force. Other studies [29,30] showed the negative effect of Er,Cr:YSGG laser irradiation on the adhesion of resin to dentin with various adhesive systems; however, acid-etching [29] after laser irradiation increased the tensile strength of the bond to dentin. In the present study, there was no difference between the Er,Cr:YSGG laser irradiation (1W, 2W and 3W) groups and the untreated group, regardless of the different root levels.…”
Section: Discussionmentioning
confidence: 97%
“…No significant difference was found between the coronal and middle levels. This finding could be due to several factors, such as regional differences in the number and density of the tubules toward the apical region of the canal, apical sclerosis, the high C-factor, the difficulty in visualization and access to the apical region, restrictions in the flow and distribution of the material and thick smear layer formation during the post space preparation [21,26,28,29,31]. Different output powers with or without water cooling were chosen in the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported higher bond strengths of filling materials following Er,Cr:YSGG laser irradiation because of phase, compositional, and microstructural changes to dentin after irradiation; 34,35 other studies have shown no difference, 36 or lower push-out bond strengths with laser irradiation use. 37 The results of the present study showed no statistically significant difference between push-out bond strengths of the group treated with Er,Cr:YSGG laser irradiation (group 2) and the group treated with EDTA + NaOCl irrigation (group 1).…”
Section: Ehsani Et Almentioning
confidence: 94%
“…Erbium laser wavelengths are transmitted through semiflexible hollow waveguides, low-OH − fiberoptic cables, or articulated arms. 4 Another disadvantage is that erbium wavelengths cannot remove gold or metal crowns, vitreous porcelain, or amalgam restorations (see Chapter 11). These wavelengths are highly absorbed by the OH − radical and thus work well in hard tissue, targeting the OH − in hydroxyapatite.…”
Section: Erbium Lasersmentioning
confidence: 99%
“…4 The use of rotary diamond or carbide burs for osseous tissue removal risks possible damage to adjacent tooth structure. Collateral thermal tissue damage when using erbium lasers is less than with conventional techniques.…”
Section: Emergence Profilementioning
confidence: 99%